Can we define patients with no chance of survival after out-of-hospital cardiac arrest?. Issue 10 (14th September 2004) - Herlitz, J; Engdahl, J; Svensson, L; Young, M; Ängquist, K-A; Holmberg, S
Abstract : Objective: To evaluate whether subgroups of patients with no chance of survival can be defined among patients with out-of-hospital cardiac arrest. Patients: Patients in the Swedish cardiac arrest registry who fulfilled the following criteria were surveyed: cardiopulmonary resuscitation (CPR) was attempted; the arrest was not crew witnessed; and patients were found in a non-shockable rhythm. Setting: Various ambulance organisations in Sweden. Design: Prospective observational study. Results: Among the 16 712 patients who fulfilled the inclusion criteria, the following factors were independently associated with a lower chance of survival one month after cardiac arrest: no bystander CPR; non-witnessed cardiac arrest; cardiac arrest occurring at home; increasing interval between call for and arrival of the ambulance; and increasing age. When these factors were considered simultaneously two groups with no survivors were defined. In both groups patients were found in a non-shockable rhythm, no bystander CPR was attempted, the arrest was non-witnessed, the arrest took place at home. In one group the interval between call for and arrival of ambulance exceeded 12 minutes. In the other group patients were older than 80 years and the interval between call for and arrival of the ambulance exceeded eight minutes. Conclusion: Among patients who had an out-of-hospital cardiac arrest and were found in a non-shockable rhythm the following factors were associated with a low chance of survival: no bystander CPR, non-witnessed cardiac arrest, the arrest took place at home, increasing interval between call for and arrival of ambulance, and increasing age. When these factors were considered simultaneously, groups with no survivors could be defined. In such groups the ambulance crew may refrain from starting CPR.